Post Conditionally Unconstitutional of Job Creation Law: Quo Vadis Legal Certainty? - A'an Efendi; Fradhana Putra Disantara (Universitas Airlangga, 2022)
Enigma emerged when the Constitutional Court declared that Law Number 11 of 2020 concerning Job Creation (UU CK) unconstitutional. The purpose of this legal research is to review the legal dynamics of the UU CK after the Constitutional Court Decision No. 91/PUU-XVIII/2020 based on the point of view of the formal review and procedural justice, as well as reviewing the relevance of the Decision as a monumental decision; while at the same time analyzing the phenomenon of 'conditionally unconstitutional' in the perspective of legal certainty and expediency. This legal research uses a conceptual approach and a statutory approach. The legal materials of this legal research consist of primary legal materials, secondary legal materials, and non-legal materials. The study results stated that the Constitutional Court Decision No. 91/PUU-XVIII/2020 is not a monumental decision, considering an omission of